PENGARUH TINGKAT PENYELESAIAN TINDAK LANJUT HASIL PEMERIKSAAN, JUMLAH TEMUAN PEMERIKSAAN LHP BPK, DAN KARAKTERISTIK PEMERINTAH DAERAH PADA OPINI ATAS LAPORAN KEUANGAN PEMERINTAH DAERAH DI PROVINSI SULAWESI SELATAN TAHUN ANGGARAN 2021-2023 - Iskak, Jamaludin; Ardinanto, Muhammad Gilang Permata (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study seeks to examine the impact of the completion rate of follow-up on audit findings, the number of audit findings from BPK (Audit Board of Indonesia), and the characteristics of local governments on the audit opinion of local government financial reports in South Sulawesi Province for the fiscal years 2021–2023. The population consists of all districts/cities in South Sulawesi Province, with samples determined using census sampling techniques. This study utilises secondary data obtained from BPK's audit reports. The analysis method employed is logistic regression analysis. The findings reveal that the follow-up completion rate, number of audit findings, and local government characteristics, including PAD, expenses, age, and assets, do not significantly influence the audit opinion. These results indicate that audit opinions are influenced more by compliance with financial reporting standards and effective internal control systems rather than by fiscal capacity or managerial experience alone.